Real options in a Ramsey style growth model - Hanno Dihle (University of Freiburg, Department of International Economic Policy (iep), 2015)
This paper studies the aggregate implications of microeconomic investment irreversibility and idiosyncratic uncertainty in a simple growth model by highlighting real option effects. We endogenize the drift rate of real option by connecting it to the state of the economy. Thereby, we extend the analysis of the optimal capital accumulation policy in the firm sector and show the different implications of idiosyncratic and aggregate uncertainty on growth dynamics.
Keywords: D81; E10; E22; O40; 330; Irreversible investment; Idiosyncratic uncertainty; real options; growth